Chemical Constituents of Mesua ferrea L. and Piper nigrum L. and Their Larvicidal Activities - Lim, Sooi Kim (2006)
Chemical and biological studies were carried out on two plants, Piper nigrum L. (Piperaceae) and Mesua ferrea L. (Guttiferae). The chemical investigations covered alkaloids, triterpenoids, carboxylic acids and anthraquinones. These compounds were isolated using common chromatographic techniques and were identified by using spectroscopic experiments such as NMR, MS, IR and UV. From the stem bark of Mesua ferrea L. two main components, betulinic acid and 1,8-dihydroxy-3-methoxy-6-methyl-anthraquinone were found in all crude extracts. In addition, stigmasterol and sitosterol were also isolated from the methanol extract. The fresh blossoms of Mesua ferrea L. gave Lup-20(29)-en-3β-ol, long chain hydrocarbons and carboxylic acids as major compounds. Meanwhile, studies on Piper nigrum L (roots) produced six alkaloids, piperlactam A and piperlactam D, one oxoarporphine (cepharadione A), piperine, sylvamide, 2,4 tetradecadienoic acid isobutyl amide, together with four carboxylic acids, tetracosanoic acid, p-hydrocinnamate ester, 2- butenedioc acid, cinnamic acid, tetracosanoic acid and benzoic acid. Two triterpenoids, stigmasterol and sitosterol were also isolated from Piper nigrum L. From the stem bark of Mesua ferrea L., although 1,8-dihydroxy-3-methoxy-6-methyl-anthraquinone (82) (Kua et al., 2006), betulinic acid (83) (Cao et al., 1997) and lup-20(29)-en-3β-ol (84) (Cao et al., 1997) were previously isolated from the family of Guttiferae, it is the first time that this class of compound has been isolated from this plant. From the roots of Piper nigrum L., there are some isolated compounds that were new to the family and few of the which are new to the species. Sylvamide (38) (Banerji et al., 1982), Cepharadione A (41) (Desai et al., 1988), Piperolactam A (46) (Desai et al., 1988) and Piperolactam D (49) (Olsen et al, 1993) has been not been isolated from Piper nigrum, but have been previously been discovered from some species of the genus Piper. This is the first time that 2,4 tetradecadienoic acid isobutyl amide (89), tetracosanoic acid, p-hydroxycinnamate esters (88) and 2-butenedioic acid, mono(2-methylpropyl) ester (87) been successfully isolated from the family of Piperaceae. All this discovery might be chemotaxonomically significant to the family. The larvicidal tests were performed against the larvae of Aedes aegypti following the WHO (1981) standard procedures with slight modifications. The crude hexane, chloroform, ethyl acetate, methanol extracts and pure piperine of Piper nigrum L showed very high toxicity activities towards the larvae by giving LC50 values of less than 2.5 μg/ml. However, the hexane, chloroform and methanol extracts of Mesua ferrea L. demonstrated lesser impact on the larvae with LC50 values higher than 150 μg/ml.